Skin-Spar Failure Detection of a Composite Winglet Using FBG Sensors - Ciminello Monica (Archive of Mechanical Engineering, 2017)
Winglets are introduced into modern aircraft to reduce wing aerodynamic drag and to consequently optimize the fuel burn per mission. In order to be aerodynamically effective, these devices are installed at the wing tip section; this wing region is generally characterized by relevant oscillations induced by flights maneuvers and gust. The present work is focused on the validation of a continuous monitoring system based on fiber Bragg grating sensors and frequency domain analysis to detect physical condition of a skin-spar bonding failure in a composite winglet for in-service purposes. Optical fibers are used as deformation sensors. Short Time Fast Fourier Transform (STFT) analysis is applied to analyze the occurrence of structural response deviations on the base of strain data. Obtained results showed high accuracy in estimating static and dynamic deformations and great potentials in detecting structural failure occurrences.